Dynamics of Water Erosion in the Aghien Lagoon Catchment - Koffi, Ehouman Serge; Dao, Amidou; Noufe, Dabissi Djibril; Ouedraogo, Mamadi; Yeo, Nagnon Bernard; Seguis, Luc; Perrin, Jean Louis; Kamagate, Bamory; Gone, Lancine Droh (European Scientific Journal, ESJ, 2024)
Soil erosion significantly impacts land quality and water resources. This paper focuses on estimating spatiotemporal changes in land-use/land-cover patterns and soil erosion in the Aghien lagoon watershed in Côte d’Ivoire. The study utilized Landsat imagery from 2016 and 2020. Images were classified into categories using supervised classification with the maximum likelihood algorithm. The Universal Soil Loss Equation (USLE) model was applied in a GIS environment to quantify potential soil erosion risk. The areas of bare soil/habitats and crops/fallow increased by 2,981 ha (37.8%) and 2,642 ha (17.58%), respectively, between 2016 and 2020. High soil losses were observed on the slopes of rivers and valleys adjacent to the Aghien lagoon, which are naturally predisposed to erosion due to the steepness, length, and inclination of the slopes. Average soil loss values were 60.65 t/ha/year in 2016 and 47.64 t/ha/year in 2020. Areas with very low and low soil loss values covered 34,441.52 ha (94.36%) in 2016 and 34,956.76 ha (95.77%) in 2020. Conversely, areas with high and very high soil losses were minimal, accounting for 0.95% and 0.60% of the watershed in 2016 and 2020, respectively. Moderate soil erosion contributed most to soil loss, affecting 1,712.19 ha (4.69%) in 2016 and 1,305.77 ha (3.58%) in 2020.